Transcriptome Profile of Fusarium graminearum Treated by Putrescine - Lina Zhang; Xishi Zhou; Pengfeng Li; Yiwei Wang; Qianyong Hu; Yuping Shang; Yunshen Chen; Xiying Zhu; Hongjie Feng; Cuijun Zhang (Journal of Fungi, 2022)
Fusarium graminearum (F. graminearum) is the main pathogen of Fusarium head blight (FHB) in wheat, barley, and corn. Deoxynivalenol (DON), produced by F. graminearum, is the most prevalent toxin associated with FHB. The wheat defense compound putrescine can promote DON production during F. graminearum infection. However, the underlying mechanisms of putrescine-induced DON synthesis are not well-studied. To investigate the effect of putrescine on the global transcriptional regulation of F. graminearum, we treated F. graminearum with putrescine and performed RNA deep sequencing. We found that putrescine can largely affect the transcriptome of F. graminearum. Gene ontology (GO) and KEGG enrichment analysis revealed that having a large amount of DEGs was associated with ribosome biogenesis, carboxylic acid metabolism, glycolysis/gluconeogenesis, and amino acid metabolism pathways. Co-expression analysis showed that 327 genes had similar expression patterns to FgTRI genes and were assigned to the same module. In addition, three transcription factor genes were identified as hub genes in this module, indicating that they may play important roles in DON synthesis. These results provide important clues for further analysis of the molecular mechanisms of putrescine-induced DON synthesis and will facilitate the study of the pathogenic mechanisms of FHB.